Synthesis of 2-aryldihydrobenzofuran neolignans and 2-arylbenzofuran neolignans and their larvicidal activities - Juhan, Siti Fadilah (2018)
2-Aryldihydrobenzofuran neolignans (tomentosanan A, ficusal, tomentosanan B) and 2- arylbenzofuran neolignans (zanthocapensole, zanthocapensate) have been isolated from the plants were synthesized and evaluated for their larvicidal activities against Crocidolimia binotalis. Two Heck coupling methods have been developed are using an activated C-I bond of iodovanillin or non-activated C-H bond of vanillin and alkene of cinnamic acid derivatives or methyl cinnamate derivatives. Heck coupling reaction between iodovanillin or vanillin with a series of cinnamic acid derivatives lead to the formation of eleven new compounds and four known compounds are 2- aryldihydrobenzofuran neolignan, 3-arylbenzofuran neolignans, 2-arylbenzofuran neolignans and stilbenes. The reaction involves a series of methyl cinnamate derivatives has resulted in the formation of five new compounds and three known compounds are lignans, neolignans, 2,3-diarylbenzofuran neolignan and coumarins. Both methods have been developed then have applied to the synthesis of five natural products of 2- arydihydrobenzofuran neolignans and 2-arylbenzofuran neolignans. All the targeted dihydrobenzofuran neolignans have synthesized as a single enantiomer form namely (+)- tomentosanan A, (+)-ficusal and (+)-tomentosanan B. Two routes have utilized to synthesize zanthocapensole and zanthocapensate and only their derivatives have been obtained from both routes. The selected compounds have been obtained from the Heck methods development and syntheses part have tested for larvicidal activity by using Crocidolomia binotalis larvae and azadirachtin as the commercial standard (LD50 = 2.818). The results indicate some of the compounds have significant activity such as dihydrobenzofuran neolignan, benzofuran neolignans, lignans, neolignans, stilbene and coumarin. Among all active compounds, (2E,3E)-dimethyl 2,3-bis(4-hydroxy-3,5- dimethoxybenzylidene)succinate (lignan) and methyl-3-(4-hydroxy-3-methoxyphenyl)-2- {2-methoxy-4[(E)-3-methoxy-3-oxo-prop-1-enyl]phenoxy}-prop-2-enoate (neolignan) have showed the strongest activity with LD50=1.678 mg/L and LD50=2.218 mg/L, respectively.